The Most Impactful Articles on the Shoulder Labrum From the United States or Europe, and Decreased Level of Evidence Is Associated With Increased Altmetric Attention Score - Amar S. Vadhera, B.S.; Lilah Fones, M.D.; William Johns, M.D.; Anne R. Cohen, B.A.; Adeeb Hanna, B.S.; Fotios P. Tjoumakaris, M.D.; Kevin B. Freedman, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2024)
Purpose: To use the top 100 articles pertaining to the shoulder labrum to understand the impact that social medial platforms have on the dissemination of shoulder research and to highlight bibliometric factors associated with Altmetric Attention Scores (AAS) to offer insight into the impact that social media platforms have on the dissemination, attention, and citation of shoulder research publications. Methods: This was a cross-sectional study. In January 2023, the Altmetric database was searched using the PubMed Medical Subject Headings terms “shoulder labrum.” Articles with the greatest AAS were screened to exclude other topics unrelated to the labrum of the shoulder. The top 100 articles that met inclusion criteria were used in the final analysis. Bibliometric factors pertaining to each study were collected for further analysis of article characteristics in accordance with previous studies. Results: The Altmetric Database query yielded 619 studies. The top 100 articles with highest AAS were identified, mean Attestation Score was 24.85 ± 55.51, with a range of 7 to 460. The included articles represented 35 journals, with 57 articles attributed to 3 journals: American Journal of Sports Medicine (AJSM; 29%), Arthroscopy: The Journal of Arthroscopic & Related Surgery (Arthroscopy; 19%), and the Journal of Shoulder and Elbow Surgery (JSES; 9%). There was a significant increase in AAS for every decrease in the numerical Level of Evidence value for a study (P = .011) but no association between score and citation rate (P > 005). Conclusions: Top articles on the shoulder labrum, as defined by high AAS score, are most commonly original clinical research published in 1 of 3 sports medicine journals and performed in the United States or Europe. A decreased numerical Level of Evidence is associated with an increase in AAS score, but there is no association between AAS score and citation rate. Clinical Relevance: The increasing amount of science and health information shared freely through open-access journals, online servers, and numerous social media channels makes it difficult to measure the impact of research. Using measures such as the Altmetric Attention Score, in isolation or addition to measures of researcher or journal impact, has the potential to provide comprehensive information about the impact of research in the modern world.